On Hecke L-functions attached to half-integral weight modular forms - Ch'oe, Yŏng-ju; Kohnen, Winfried (Journal of number theory, 2018)
We investigate non-vanishing properties of L(f,s) on the real line, when f is a Hecke eigenform of half-integral weight k+12 on Γ0(4).
Gesehen am 08.02.2019